Novel Approach of IC-Based User Defined Temperature Control System - Mondal, Bikas; Chaudhuri, Archibrata; Billaha, Aref; Roy, Bhaskar; Datta, Promana (International Journal of Computer Sciences and Engineering, 2025)
Temperature is one of the most important process variables which are required to be measured and as well as controlled in the field of different process industries. So, accurate and reliable measurement of temperature is always treated as one of the most essential requirements in any process industry. The main objective of this work is to design and implement an automated user-defined temperature control system using the IC-based temperature sensor and embedded system. In order to control the temperature of a system in a very compact way,the temperature window should be user-defined. An automatic temperature controlling system is a device that helps keep the temperature of a particular region within a defined temperature window. A temperature window selects the range of temperature where the lower limit and the upper limit of the temperature is user-defined. This means the temperature window within which the temperature is to be maintained purely depends on the user. Any time the user can change the set temperature range accordingly. It is generally used for measurement as well as controlling the temperature within the range of -55oC to 150oC.